Intergenerational Justice in Public Finance: A Canadian case study - Paul Kershaw (Intergenerational Justice Review)
This study examines whether Canadian governments have adapted budgets for the ageing population in accordance with norms of intergenerational justice. Public finance data in 2016 are analysed compared to 1976 in light of three constructs: the elderly/non-elderly ratio of social spending change, intergenerational reciprocity, and ability to pay. Findings include that (i) governments increased per capita spending for seniors 4.2 times faster than for those under the age of 45; (ii) public finance requires younger Canadians to contribute 22%-62% more in income taxes for the elderly now by comparison with 1976; and (iii) the contemporary ageing population has a greater ability to pay than cohorts immediately before and after them.